(untitled) - Rullhusen, P. (Singapore, 1998)
The purpose of this book is to give a description of the state of the art in theoretical and experimental work achieved in radiation source development. It summarizes clearly and comprehensibly, the basic physical aspects needed to understand the phenomena, and also provides the interested reader with sufficient literature to be able to follow the development in more detail.
Keywords: Electrons,X-rays,Nguồn bức xạ,E-léc-tron,X-quang,Radiation sources